2008
DOI: 10.1149/1.2816329
|View full text |Cite
|
Sign up to set email alerts
|

Additive-Gas Effects on Cl[sub 2] Plasma-Based Copper-Etch Process and Sidewall Attack

Abstract: The influence of the additive gas in Cl 2 plasma-based copper etch and sidewall attack was investigated. The additive gas, such as Ar, N 2 , and CF 4 , drastically changed the plasma-phase chemistry, i.e., the Cl radical concentration, and the ion-bombardment energy, which resulted in changes of the copper chlorination rate and the sidewall roughness. The addition of Ar increased the Cl concentration, which increased the copper chlorination rate and the sidewall attack. The addition of N 2 enhanced ion bombard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…5 Second, the Ta barrier layer was etched with the CF 4 plasma, which did not attack the Cu sidewall. 21 After the photoresist layer was stripped off, the complete Cu line was defined. Finally, a plasma-enhanced chemical vapor deposition ͑PECVD͒ SiN x layer, which prevented Cu from oxidation during the EM test, was deposited on the patterned Cu sample.…”
Section: Methodsmentioning
confidence: 99%
“…5 Second, the Ta barrier layer was etched with the CF 4 plasma, which did not attack the Cu sidewall. 21 After the photoresist layer was stripped off, the complete Cu line was defined. Finally, a plasma-enhanced chemical vapor deposition ͑PECVD͒ SiN x layer, which prevented Cu from oxidation during the EM test, was deposited on the patterned Cu sample.…”
Section: Methodsmentioning
confidence: 99%
“…The same phenomenon was observed in the Cl 2 /N 2 plasma exposed Cu chlorination reaction. 6 Actually, it is difficult to separate the above two factors because they can influence each other. For example, it was observed that the high-porosity CuCl x film contained a larger Cl concentration than the low-porosity CuCl x film during room- …”
Section: Resultsmentioning
confidence: 99%
“…4 Formation rates of CuCl x and CuBr x as well as their morphologies are related to plasma parameters, such as gas composition, pressure, power, and substrate temperature. 3,5,6 Submicrometer Cu lines have been successfully fabricated with this method. 7 Thus far, most studies were carried out on the as-deposited Cu film ͑i.e., the grain size and microstructure were fixed͒.…”
mentioning
confidence: 99%
“…The photoresist patterned Cu film was exposed to a Cl 2 -containing plasma and then dipped into a dilute HCl solution (34,35,36). The complete Cu line is defined after etching off the Ta barrier layer with a CF 4 plasma and stripping off the photoresist layer.…”
Section: Cu Lines Prepared From the Plasma-based Etching Process And mentioning
confidence: 99%